Perancangan Glamping dengan Konsep Ekologis dalam Pengembangan Fasilitas di Kawasan Wisata Pantai Mutiara - Elby Putra Adrie Loho; Diyah Ayu Saputri (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The development of sustainable tourism facilities is one of the important efforts in increasing the attractiveness of destinations while preserving the environment. This study aims to analyze the implementation of ecological concepts in the development of glamping facilities in the Pearl Beach tourist area. The method used is a descriptive qualitative approach, with data collection through field observations, interviews with managers and tourists, and literature studies related to ecotourism principles and sustainable design. The results of the study show that the application of ecological concepts in glamping facilities in Mutiara Beach includes the use of environmentally friendly materials, integrated waste management, the application of energy efficiency, and designs that integrate the natural landscape without damaging the coastal ecosystem. The application of this concept not only improves the comfort and experience of tourists, but also contributes to increasing environmental awareness and strengthening the positive image of tourist destinations. In addition, this ecologically-conceptual glamping development model is expected to be a reference for the development of sustainable tourism facilities in other coastal areas, which prioritizes nature preservation and the welfare of local communities.